Signalling pathways underlying pulsed electromagnetic fields in bone repair - Wang, Aoao; Ma, Xinbo; Bian, Jiaqi; Jiao, Zhenrui; Zhu, Qiuyi; Wang, Peng; Zhao, Yantao (Frontiers in Bioengineering and Biotechnology, 2024)
Pulsed electromagnetic field (PEMF) stimulation is a prospective non-invasive and safe physical therapy strategy for accelerating bone repair. PEMFs can activate signalling pathways, modulate ion channels, and regulate the expression of bone-related genes to enhance osteoblast activity and promote the regeneration of neural and vascular tissues, thereby accelerating bone formation during bone repair. Although their mechanisms of action remain unclear, recent studies provide ample evidence of the effects of PEMF on bone repair. In this review, we present the progress of research exploring the effects of PEMF on bone repair and systematically elucidate the mechanisms involved in PEMF-induced bone repair. Additionally, the potential clinical significance of PEMF therapy in fracture healing is underscored. Thus, this review seeks to provide a sufficient theoretical basis for the application of PEMFs in bone repair.